1987
DOI: 10.1017/s0016672300026720
|View full text |Cite
|
Sign up to set email alerts
|

Five of the nine genetically defined regions of mousethaplotypes are involved in transmission ratio distortion

Abstract: SummaryMouse t haplotypes have been divided into nine subregions that are each defined by one or more molecular markers. In previous studies, three of these subregions were shown to contain ‘distorter loci’ that interact to effect the transmission-ratio distortion phenotype characteristic of all complete t haplotypes. To determine which of the remaining six subregions also play a role in this phenotype, we analysed the accumulated data on transmission ratio distortion from males that carried one of 26 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 23 publications
1
41
2
Order By: Relevance
“…Finally and most germane to the results presented here are previous genetic studies showing a connection between TCP-1 and microtubule-related phenomenon. In the mouse, where the TCP-1 locus was first identified, mutations in the locus were always associated with transmission ratio distortions (11), perhaps indicative of microtubule abnormalities. In addition, the TCP-1 protein was shown to be expressed at high levels during spermatogenesis, a process that requires the assembly of complex macromolecular structures, including the microtubule core of the flagellum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally and most germane to the results presented here are previous genetic studies showing a connection between TCP-1 and microtubule-related phenomenon. In the mouse, where the TCP-1 locus was first identified, mutations in the locus were always associated with transmission ratio distortions (11), perhaps indicative of microtubule abnormalities. In addition, the TCP-1 protein was shown to be expressed at high levels during spermatogenesis, a process that requires the assembly of complex macromolecular structures, including the microtubule core of the flagellum.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, expression of TCP-1 increases markedly during spermatogenesis (10), a process that requires the assembly of complex macromolecular structures including the microtubule core of the flagellum. In addition, mutations within the TCP-1 locus are associated with both microtubule abnormalities and transmission ratio distortions (11). Similarly in yeast, temperaturesensitive mutations of the TCP-1 gene result in a number of alterations in microtubule mediated processes.…”
mentioning
confidence: 99%
“…For additional evidence that t""j contains no wild-type T66 genes, note the absence of wrild-type fragments in Figure 2A. 1984;LYON 1986;SILVER and REMIS 1987).…”
Section: Discussionmentioning
confidence: 99%
“…and the t complex responder. Tcr (LYON 1984: SILVER andREMIS 1987). Tcd-2 is located somewhere between T66C and the distal end of the t complex.…”
mentioning
confidence: 99%
“…1A;Lyon 2003). However, rare recombinants have been isolated and utilized to identify and map four Distorter loci (t-complex distorters 1-4, Tcd1-4) and the single Responder (t-complex responder, Tcr) to chromosomal subregions of several megabases (Lyon 1984;Silver and Remis 1987). Genetic data demonstrated that Tcd loci act additively in enhancing the transmission rate of Tcr.…”
mentioning
confidence: 99%